Differential metabolomic pathway analysis in Malaysian childhood acute lymphoblastic leukemia patients treated with high-dose methotrexate - Rizal Husaini Razali; Lay Kek Teh; Mohd Zaki Salleh; Kok Hoi Teh; Hishamshah Mohd Ibrahim (Elsevier, 2024)
Background: Methotrexate (MTX) is the mainstay of the consolidation and maintenance phase of chemotherapy protocol for childhood acute lymphoblastic leukemia (ALL). This study aimed to investigate the altered metabolism associated with high dose-MTX and determine the potential of the metabolic markers and differential pathways involved in MTX therapy. Methods: Serum samples were collected from 38 children with ALL at 2 time points: p-MTX; before induction chemotherapy was initiated, and post-MTX; after completion of the first high-dose MTX. The samples were analyzed using HPLC/MS-QTOF. Data acquisition was performed using Agilent MassHunterTMB.05.00 software for subsequent metabolomics analysis. Differential expressions of metabolites were analyzed using univariate Welch's t-test unequal variance. Compounds were identified using the METLIN Database. Pathways and network analyses were performed using Metaboanalyst 4.0. Potential biomarkers were analyzed using the Receiving Operator Characteristic curve. Results: Metabolites with AUC between 0.7 and 0.9 include xanthine (0.889), oxoglutaric acid (0.770), and alpha-linolenic acid (ALA) (0.741). Alpha-linolenic acid abundance was detected in ALL patients with remission status, corresponding to a test sensitivity and specificity of 0.77 and 0.87, respectively. ALA has an antineoplastic effect that potentially inhibits the proliferation of leukemic cells by inhibiting caspase activation in the phosphatidylinositol 3-kinase (PI3K) pathway and Bcl-2 inhibition. Conclusion: In this study, ALA was found to be significantly higher in patients treated with high-dose MTX and associated with remission status than in pre-MTX treatment.